APRIL 2010 IN KYRGYZSTAN: AS SEEN FROM KAZAKHSTAN - LAUMULIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2010)
In April 2010, the political crisis that has been simmering in Kyrgyzstan over the past few years developed into an armed confrontation between the government and the people, as well as among the various clan and regional groups at the very top of the republic’s political pyramid.1 President Bakiev, deprived of his power (at first in part), legitimacy, and control over the country, tried to regain what he had lost by tapping the political resource of the country’s South. The events that occurred in May made it abundantly clear that a large-scale political conflict, a civil war, and a split in the republic were only a step away. The 2005 events, which toppled Akaev’s regime, demonstrated that for its continued political development, the republic must acquire a strong vertical of power and move toward a strong presidential government, which alone could pull the country out of the crisis and set it on the path of sustainable development.2 The compromise reached (which, albeit, proved incomplete) gave rise to the hope that the new president would be able to cope with this historic mission.3